A Mild and General One‐Pot Synthesis of Densely Functionalized Diaryliodonium Salts. Issue 27 (September 2015) - Qin, Linlin; Hu, Bao; Neumann, Kiel D.; Linstad, Ethan J.; McCauley, Katelyenn; Veness, Jordan; Kempinger, Jayson J.; DiMagno, Stephen G.
Abstract: Diaryliodonium salts are powerful and widely used arylating agents in organic chemistry. Here we report a scalable synthesis of densely functionalized diaryliodonium salts from aryl iodides under mild conditions. This two‐step, one‐pot process has remarkable functional group tolerance, is compatible with commonly employed acid‐labile protective group strategies, avoids heavy metal and transition metal reagents, and provides a direct route to stable precursors to PET imaging agents. Abstract : One‐pot synthesis of complex, unsymmetrical diaryliodonium salts: A mild and general approach to densely functionalized diaryliodonium salts is described. This two‐step process has remarkable functional group tolerance, and it is compatible with commonly employed acid‐labile protective group strategies.